A Strong and Resilient Research System is Built by Valuing People - Elshire, Robert (New Zealand Science Review, 2022)
The New Zealand public research system is undergoing a once in a generation review and renewal. This piece reflects on past working conditions, describes the current situation, and provides some possibilities for improvement.